MAKNA PEPINDHAN MANUSIA DALAM PANYANDRA UPACARA PANGGIH PENGANTIN ADAT JAWA RAGAM SURAKARTA - Anggyta Aulia Rahma Nardilla (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2021)
This research discusses the types and meanings of human's pepindhan from Javanese panyandra wedding ceremony Surakarta’s style in Rejoso Village, Rejoso District, Nganjuk Regency, East Java. The types and the meaning’s theory from pepindhan manusia of Javanese panyandra wedding ceremony Surakarta’s style in Rejoso Village in this research comes from Padmosoekotjo, Aloysius, and Halley. This qualitative descriptive study using a stylistic approach method. The object of this research is the utterances from Mr. Sujarwo and Mr. Wasito's speech as a famous Master of Ceremony (MC) in Rejoso Village. Data collected through the observations and analyzed by Miles and Huberman’s analysis. Data’s step analysis from this research through data reduction, presentation data, and verification analysis. Data validity is attempted through triangulation and validity checking. The results of this research indicated that the types of human’s pepindhan were found in the Javanese panyandra wedding ceremony Surakarta’s style in Rejoso Village, Rejoso District, Nganjuk Regency, East are similes and metaphors. The meaning of human’s pepindhan in this research means perfection, luxury, glorious, and beauty from the description of the situation, bridesmaids, conditions, and the good prayers for the household of the bride and groom.Penelitian ini membahas tentang jenis dan makna pepindhan manusia dalam panyandra upacara panggih pengantin adat Jawa ragam Surakarta di Desa Rejoso, Nganjuk, Jawa Timur. Jenis dan makna pepindhan manusia dalam panyandra upacara panggih pengantin adat Jawa ragam Surakarta di Desa Rejoso pada penelitian ini menggunakan teori dari Padmosoekotjo, Aloysius, dan Halley. Penelitian deskriptif kualitatif ini menggunakan metode pendekatan stilistika. Objek kajian dalam penelitian ini ialah tuturan dari pewara terkenal di Desa Rejoso yaitu Bapak Sujarwo dan Bapak Wasito. Data pada penelitian ini dikumpulkan melalui observasi lapangan dan dianalisis menggunakan analisis data Miles dan Huberman. Tahapan analisis data penelitian ini dilakukan dengan tahap analisis reduksi data, penyajian data, dan verifikasi. Keabsahan data pada penelitian ini menggunakan triangulasi data dan pemeriksaan validitas oleh ahli bidang. Hasil dari penelitian ini menunjukan adanya jenis pepindhan manusia yang ditemukan pada panyandra upacara panggih pengantin adat Jawa ragam Surakarta di Desa berupa simile dan metafora. Makna dari pepindhan manusia pada penelitian ini berarti kesempurnan, kemewahan, kesakralan, dan keindahan dari penggambaran keadaan pada resepsi pernikahan, pengiring pengantin, kondisi acara, dan doa yang baik untuk rumah tangga dari pengantin.